Land cover transitions and effects of transhumance on available forage biomass of rangelands in Benin - James Ellison; Katja Brinkmann; Rodrigue V. Cao Diogo; Andreas Buerkert (Environment, Development and Sustainability, 2021)
This study examined the effects of transhumance pressure on total abavoe-ground biomass and forage availability on rangelands in Benin. We also investigated the implications of land cover transitions on rangelands over a 31-year period. Our work was carried out in three regions of Benin representing distinct phytogeographic regimes: Ketou, Tchaourou, and Sinende. Ground-truthing and biomass sampling of the herbaceous and phanaerophyte strata were carried out between the 2016 peak vegetation period and the onset of the 2017 rainy season. Herbaceous biomass was determined by destructive sampling, and biomass of shrub and trees was estimated using non-destructive sampling and allometric equations. Historical and present-day Landsat data allowed an analysis of land cover change for the 1986–2002 and 2002–2017 periods. Land cover analyses yielded evidence of significant expansion of agricultural areas, especially in the latter period. The data also revealed progressive landscape fragmentation and transformations to a land cover of reduced total phytomass. There were no long-term effects of transhumance on trees, but likely on herbaceous biomass. Land cover changes in the study regions seem primarily the result of population pressure, infrastructural changes, persisting norms, and traditions regarding environmental management and the increasing popularity of livestock keeping as an insurance strategy. Rangeland transformations had negative impacts on transhumant herds' mobility and forage availability. As rangeland stability and consent between agricultural and pastoral land users are at a tipping point, informed policies, and land use planning that foster compromises among all stakeholders are needed.
Keywords: 330; Allometric equations; Biomass estimation; Land cover changes; Landsat; Transhumant pastoralism